Suppressing Surface Lattice Oxygen Release of Li‐Rich Cathode Materials via Heterostructured Spinel Li4Mn5O12 Coating. Issue 29 (28th May 2018) - Zhang, Xu‐Dong; Shi, Ji‐Lei; Liang, Jia‐Yan; Yin, Ya‐Xia; Zhang, Jie‐Nan; Yu, Xi‐Qian; Guo, Yu‐Guo
Abstract: Lithium‐rich layered oxides with the capability to realize extraordinary capacity through anodic redox as well as classical cationic redox have spurred extensive attention. However, the oxygen‐involving process inevitably leads to instability of the oxygen framework and ultimately lattice oxygen release from the surface, which incurs capacity decline, voltage fading, and poor kinetics. Herein, it is identified that this predicament can be diminished by constructing a spinel Li4 Mn5 O12 coating, which is inherently stable in the lattice framework to prevent oxygen release of the lithium‐rich layered oxides at the deep delithiated state. The controlled KMnO4 oxidation strategy ensures uniform and integrated encapsulation of Li4 Mn5 O12 with structural compatibility to the layered core. With this layer suppressing oxygen release, the related phase transformation and catalytic side reaction that preferentially start from the surface are consequently hindered, as evidenced by detailed structural evolution during Li + extraction/insertion. The heterostructure cathode exhibits highly competitive energy‐storage properties including capacity retention of 83.1% after 300 cycles at 0.2 C, good voltage stability, and favorable kinetics. These results highlight the essentiality of oxygen framework stability and effectiveness of this spinel Li4 Mn5 O12 coating strategy in stabilizing the surface of lithium‐rich layered oxides against lattice oxygen escaping for designing high‐performance cathode materials for high‐energy‐density lithium‐ion batteries. Abstract : A heterostructured spinel Li4 Mn5 O12 encapulated lithium‐rich layered oxide cathode is designed by the controlled KMnO4 oxidiation strategy. Spinel Li4 Mn5 O12 is chosen due to its lattice stability against oxygen release as well as a 3D lithium diffusion framework with minimal Jahn–Teller distortion. Such uniform coating can suppress lattice oxygen release, associated phase transformation, and catalytic side reactions, consequently ensuring improved electrochemical performance.